Comparative study of micro ESR with CRP and blood culture sensitivity - Angadi, Bhavana M.; Rangaswamy, Shalini S. (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal sepsis is one of the leading causes of morbidity and mortality among neonates in India. Indian association of paediatrics has developed sepsis screen which is useful for early diagnosis. To test the reliability of micro ESR as bedside tool in early diagnosis of neonatal sepsis we conducted this study. Comparison of Micro-erythrocyte sedimentation rate (micro ESR) with C-reactive protein (CRP) and blood culture sensitivity in neonatal sepsis. To establish a relation between severity of sepsis and Micro-erythrocyte sedimentation rate. Methods: This is a cross sectional study done at neonatal intensive care unit (NICU), at our institute over a period of six months. Fifty neonates with risk factors for sepsis and who had a positive sepsis screen were enrolled prospectively into the study. Results: Out of 50 samples collected, micro ESR (>15 mm/hour) was positive in 12 cases (24%) and CRP was positive in 18 cases (36%). After procuring the blood culture report, 48 cases had neonatal sepsis (84%). Our study showed that micro-ESR as a bedside test had a positive correlation with mortality (p value <0.001) when compared with CRP values (p value=0.546) in neonatal sepsis. As expected, elevated micro ESR and high CRP value had 100% correlation but was not statistically significant (p=0.319). In all the 12 cases with raised micro ESR had 100% blood culture positivity but significance could not be established. Conclusions: Micro-ESR had a significant correlation with mortality in neonatal sepsis.